2008
DOI: 10.1177/112067210801800316
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Results of Viscocanalostomy

Abstract: Viscocanalostomy appears to be a safe and effective intraocular pressure lowering procedure in eyes with primary open angle glaucoma and certain types of secondary open angle glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…IOP significantly reduced from a mean of 21.6 to 16.4 mm Hg after LGP. 11 Shaarawy et al 6 studied the outcomes of 57 nonrandomized eyes that underwent VC, with a mean followup of 64.1 months. In total, 37% (21 patients) required…”
Section: Discussionmentioning
confidence: 99%
“…IOP significantly reduced from a mean of 21.6 to 16.4 mm Hg after LGP. 11 Shaarawy et al 6 studied the outcomes of 57 nonrandomized eyes that underwent VC, with a mean followup of 64.1 months. In total, 37% (21 patients) required…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] NPGS procedures can result in a significant reduction of IOP over extended periods of time with few complications. These reports confirm the need for LGP in maintaining long-term IOP control.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies reported that non-penetrating trabecular surgery is more effective in lowering IOP [18][19][20][21] , but other prospective researches concluded that the two procedures were similar in terms of IOP-reducing effect [22][23][24] . This study, by conducting a Meta analysis on the IOP-lowering effect of two operations 10 months after operation and at the censoring time, showed that there were statistically significant differences in IOP-reducing effect at different time points after operation between non-penetrating trabecular surgery and traditional trabeculectomy, i.e., the non-penetrating surgery could achieve better IOP-lowering effect at various postoperative time points as compared with its penetrating procedure.…”
Section: Efficacies Of the Glaucoma Surgeries 321 Iop-reducing Effementioning
confidence: 99%